Multiple Types of Porosity – P‐Wave Velocity Relationships for the Nankai Trough. Issue 7 (1st July 2022) - Yabe, S.; Hamada, Y.; Kitamura, M.; Fukuchi, R.; Hashimoto, Y.
Abstract: The empirical relationship between the porosity and P‐wave velocity is a useful tool for probing large‐scale underground physical properties and stress states based on P‐wave velocity structures acquired by seismic surveys. In this study, the porosity‐velocity curves were examined using local core sample and logging datasets acquired along the Kumano transect in the Nankai Trough, Southwest Japan. We tested Hashimoto et al.'s (2010) hypothesis that slope apron and accreted sediments have different relationships. Our advantage is using a large amount of logging and core data obtained at multiple sites in the Nankai Trough under various geological conditions, from the incoming oceanic plate to the inner wedge. We identified multiple types of porosity – P‐wave velocity relationships: 1) The first type agrees with the low‐velocity model in the global empirical relation of Erickson and Jarrard 1998), which is observed at lithostatic stress state condition (incoming upper Shikoku basin and slope sediments), 2) The second type consistent with high‐velocity models of the global empirical relation observed at compressive stress state condition (accreted sediments), which have a higher velocity and larger dependence on the porosity than the first type with the same porosity, and 3) The third type for incoming sediments with high smectite content has lower velocity than the first type. Based on our results, the transition between the first and second porosity – velocity relationships occurs in the prism toe, implying that compressive stress due to subduction controls acoustic properties and the lithification process of these sediments. Plain Language Summary: Physical properties of rocks in subduction zones are important factors controlling genesis of earthquakes. Among many kinds of physical properties, this study focuses on the relationship between porosity and P‐wave velocity at the Nankai Trough, Southwest Japan. As this relationship is affected by how the soft sediments are lithified through the subduction process, it has been studied frequently to understand physical properties and stress states of geological formations around plate boundary faults. This study compiles P‐wave velocity datasets acquired by scientific drilling projects in offshore regions, as well as porosity datasets. We tested the hypothesis proposed by a previous study that there are two types of the relationships between the two quantities. We find these two types are consistent with the global empirical relationships observed at lithostatic and compressive stress states respectively. The former includes sediments on the oceanic plate before subduction and slope apron sediments. The latter are sediments accreted toward the Japan arc. We also find that the transition from the former to the latter occurs in the sediments at the tip of accretionary prism. This suggests that compressive stress state due to subduction plays an important role in controlling the acoustic properties of sediments. Key Points: Porosity and P‐wave velocity data were compiled to investigate their relationships at the Kumano transect in the Nankai Trough Accreted sediments have higher P‐wave velocity compared with incoming and slope apron sediments with the same porosity The stress state in the accretionary prism might be a factor controlling the porosity – P‐wave velocity relationships of sediments